Development and Sensory Evaluation of Oat–Spinach Chicken Meatballs (SOATYAM) - Eka Devi Aryanti; Tarishah Asathin; Fathma Syahbanu (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Diabetes mellitus (DM) prevalence continues to rise both globally and in Indonesia, creating a need for food alternatives that are safe for blood glucose control. Meatball (bakso) is widely consumed in Indonesia but is typically high in fat and low in fiber, limiting its suitability for people with DM. This study aimed to analyze the organoleptic properties of chicken meatball formulated with oat flour and varying concentrations of spinach flour (SOATYAM) and to determine the most accepted formula among three treatments. A completely randomized design was used with three spinach flour concentrations, 5 g (F1), 10 g (F2), and 15 g (F3), combined with a constant proportion of oat flour. Sensory evaluation was conducted by 10 semi-trained panelists who rated the color, aroma, taste, texture, and aftertaste of all three formulas using a 5-point hedonic scale. Data were analyzed using the Friedman test, appropriate for repeated-measures sensory data, followed by Wilcoxon signed-rank post-hoc tests with Bonferroni correction where applicable. No significant differences were found among the three formulas for any sensory attribute (p>0.05). F1 consistently received the highest mean hedonic scores across all attributes, including overall acceptance (3.54 ± 0.70), followed by F2 (3.28 ± 0.82) and F3 (2.86 ± 0.79). These findings indicate that F1, containing the lowest proportion of spinach flour, was the most accepted formula and represents a promising functional food alternative for people with diabetes mellitus, although further studies on its nutritional composition, glycemic index, and shelf life are recommended.